Impact of forest disturbance on the structure and composition of vegetation in tropical rainforest of Central Sulawesi, Indonesia - RAMADHANIL PITOPANG (Society for Indonesian Biodiversity, 2012)
Pitopang R. 2012. Impact of forest disturbance on the structure and composition of vegetation in tropical rainforest of Central Sulawesi,Â Indonesia. Biodiversitas 13: 178-189. We presented the structure and composition of vegetation in four (4) different land use types namely undisturbed primary forest, lightly disturbed primary forest, selectively logged forest, and cacao forest garden in tropical rainforest margin of the Lore Lindu National Park, Central Sulawesi Indonesia. Individually all big trees (dbh > 10 cm) was numbered with tree tags and their position in the plot mapped, crown diameter and dbh measured, whereas trunk as well as total height measured by Vertex. Additionally, overstorey plants (dbh 2- 9.9 cm) were also surveyed in all land use types. Identification of vouchers and additional herbarium specimens was done in the field as well as at Herbarium Celebense (CEB), Tadulako University, and Nationaal Herbarium of Netherland (L) Leiden branch, the Netherland. The result showed that the structure and composition of vegetation inÂ studied are was different. Tree species richness was decreased from primary undisturbed forest to cacao plantation, whereas tree diversity and its composition were significantly different among four (4) land use types. Palaquium obovatum, Chionanthus laxiflorus, Castanopsis acuminatissima, Lithocarpus celebicus, Canarium hirsutum, Euonymus acuminifolius and Sarcosperma paniculatum being predominant in land use type A, B and C and Coffea robusta, Theobroma cacao, Erythrina subumbrans, Gliricidia sepium, Arenga pinnata, and Syzygium aromaticum in the cacao plantation. At the family level, undisturbed natural forest was dominated by Fagaceae and Sapotaceae disturbed forest by Moraceae, Sapotaceae, Rubiaceae, and agroforestry systems by Sterculiaceae and Fabaceae.